Missed opportunities for cervical screening at Worcester Hospital and Worcester Community Health Centre, Worcester, South Africa - Daniel S. Mphatsoe; Michael K. Pather (South African Family Practice)
Background: Cervical cancer is the only gynaecological malignancy for which a screening modality is widely accepted and recommended for all women.1 Just as in other developed countries, the decline in deaths from cervical cancer in the white population in South Africa after the mid-1960s has been attributed to cytological screening.2 The purpose of this study was to determine the extent of missed opportunities for cervical cancer screening by the healthcare service at Worcester Hospital and the closely associated Worcester Community Health Centre (CHC) for patients 30 years and older who presented at these centres for reasons unrelated to cervical cancer screening.